Pengaruh Pengawasan Pimpinan, Disiplin Kerja, dan Kompetensi Terhadap Kinerja Pegawai Pada Inspektorat Kabupaten Brebes - Asyaroh, Laelly; Amalia, Mei Rani (Major Management, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2022)
Human resources are one of important factors in an organization and are understood as strengths that come from human potential and can help to achieve organizational goals. Employee performance in a government agency is influenced by various factors originating from internal and external, these factors include leadership supervision, work discipline, competence. If the resulting performance is good, it will also have a good impact on a government institution.This study aims (1) to determine the effect of supervision on the performance of the Brebes Inspectorate employees (2) to determine the effect of supervision on the performance of the Brebes Inspectorate employees (3) to determine the effect of competence on the performance of the Brebes Inspectorate employees (4) to determine the effect of leadership supervision, work discipline, competence on the performance of employees of the Brebes Inspectorate. This research is categorized as a survey research, where the research instrument is a questionnaire and uses a Likert scale. The population in this study were all employees of the Brebes Inspectorate who found 46 people. The sampling technique used was purposive sampling because 37 samples were taken with non-structural official criteria. The research method used is primary data with a quantitative approach. The data analysis method used is multiple linear regression analysis. The results of this study indicate that: (1) leadership supervision partially affects employee performance with a significant value (0.000 <0.05). (2) work discipline partially affects employee performance with a significant value (0.002 <0.05). (3) competence partially affects employee performance with a significant value (0.000 <0.05). (4) leadership supervision, work discipline, competence simultaneously affect employee performance with a significant value (0.000 <0.05).